Meningkatkan Kemampuan Merencanakan dan Melaporkan Hasil Penelitian tentang Faktor Luar Pertumbuhan Tanaman Melalui Analisis Jurnal Ilmiah - Utami, Asta Puji (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
The difficulties of class XII students in learning Biology at 3.1 / 4.1 Basic Competence are designing, conducting and reporting the results of research on the influence of external factors on plant developments, orally or in writing. This is because the material is very complex related to KD in class X, XI and XII. The teacher offers a solution to this problem by assigning students to analyze the ISSN research journal about plant growth and productivity. The implementation of this method is carried out in the KD learning from the 2017/2018 to 2020/2021 academic year where the results are observed by the teacher from the stages of designing, implementing to reporting the results of research orally or in writing. The data was strengthened by questionnaires on 81 students in the span of the academic year via google form. The results obtained can be concluded that all groups of students have no difficulty in designing to presenting research results, students are actively consulted during the research, to preparing reports. The absorption of related indicators in UNBK for students of SMAN 1 Bantul increased, namely 74.07 then 75.00 and in the 2018/2019 academic year it reached 100%. There are many benefits felt by students who are explored through questionnaires, namely they can design (determine and how to write titles, formulate problems, hypotheses, determine research variables, determine topics in literature reviews) to report research results with relatively few obstacles, are motivated to carry out the task because get a detailed description of research, feel happy with additional insight into new concepts, understand the relationship between concepts, use journals as a new reference source, teamwork, present formally, are able to answer questions, and have curiosity about other group research, so learning not boring.